Still Feeding the World? The Political Ecology of Canadian Prairie Farmers - Müller, Brigit (Anthropologica, 2022)
This article examines how many Saskatchewan farmers came to think of themselves as independent farmer-entrepreneurs who had to control nature and the market by using the latest agricultural technology and by becoming astute players on the world market. The article draws on Innis’s staple theory to understand how large-scale export agriculture structures farmers’ "fields of possible action" in a thoroughly intervened and produced nature and on Foucault’s writings on neoliberal governance to comprehend their subjective responses. Beyond the classical enquiry of anthropological political economy, this article focuses on the relationship of farmers to nature as an intensely political one.